A Study on Scope/Opportunities, Constraints and Strategies for Growing Redsandalwood Trees in Laterite Soils of District Purulia in West Bengal - Planning Commission (Planning Commission)
The Planning Commission, Govt, of India has given due emphasis to the development of Agriculture by resolving the farmers with a view to increase Production of the Country as a whole. There has been a distinct change from the traditional commodity oriented culture to area specific agriculture considering the potential of the area, their constraints, local needs by adopting Agro-climatic Regional Planning (ACRP) approach.
Planning Commission, Government of India